1, 3, 5‐Triphenylpyrazoline Based Fluorescent Probe for Selective Sensing and Imaging of Glutathione in Live Cell under Oxidative Stress. Issue 2 (10th January 2020) - Subramaniyan, Siva Bala; Annes, Sesuraj Babiola; Yuvasri, Manokaran; Nivedha, Kolanchinathan; Ramesh, Subburethinam; Anbazhagan, Veerappan
Abstract: Herein, a facile method to synthesize the fluorescence probe 1‐(4‐(1, 5‐diphenyl‐4, 5‐dihydro‐1H‐pyrazol‐3‐yl)phenyl)‐1H‐pyrrole‐2, 5‐dione (probe 10 ) was reported. The relative quantum yield determined using quinine sulfate for the probe 10 is 42% in 100% acetonitrile (ACN), which was reduced to 6% in 10% ACN‐water system. The turn‐off probe 10 becomes turn‐on selectively in the presence of glutathione (GSH). The Probe 10 is highly sensitive to GSH in the presence of common interfering molecules like cysteine, N ‐acetylcysteine, thioglycolic acid, mercaptoethanol, and mercaptopropionoic acid. The limit of detection is 0.06 μM. The practical use of the probe 10 was demonstrated through quantifying GSH (1.68 mM) in the blood serum of healthy person, artificial cerebrospinal fluid, and artificial urine. Probe 10 works on a wide range of pH 2–12. Cells expressing GSH can be imaged using probe 10 and also useful in analysing the percentage of GSH in the cells under oxidative stress. Abstract : Fluorescence of probe 10 turn‐off by water and turn‐on by GSH – useful for imaging live cell and for the sensing in biological fluids